Development and In Vitro Characterization of Hyaluronic Acid-Based Coatings for Implant-Associated Local Drug Delivery Systems - Svea Petersen; Sebastian Kaule; Michael Teske; Ingo Minrath; Klaus-Peter Schmitz; Katrin Sternberg (Journal of Chemistry)
The development of drug-eluting coatings based on hyaluronic acid (HA) is especially promising for implant-associated local drug delivery (LDD) systems, whose implantation provokes high insertion forces, as, for instance, cochlear implants or drug-coated balloons (DCB). The lubricious character of HA can then reduce the coefficient of friction and serve as drug reservoir simultaneously. In this context, we investigated several plasma- and wet-chemical methods for the deposition of HA-based coatings with LDD function on polyamide 12 as a model implant surface, conventionally used for DCB. In contrast to aminosilane, epoxy silane surface layers allowed the covalent attachment of a smooth and uniform HA base layer, which provided good adherence of further HA layers deposited by manual dip coating at a subsequent processing stage. The applied HA-crosslinking procedure during dip coating influences the transfer and release of paclitaxel, which could be reproducibly incorporated via infiltration. While crosslinking with N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide hydrochloride provided HA coatings on DCB, which allowed for an efficient paclitaxel transfer upon expansion in a vessel model, crosslinking with glutardialdehyde resulted in a slower drug release being more appropriate for implants with longer residence time in the body. The developed HA coating is hence well suited for spontaneous and sustained LDD.